Cardiac Troponin Mutations and Restrictive Cardiomyopathy. (8th June 2010) - Parvatiyar, Michelle S.; Pinto, Jose Renato; Dweck, David; Potter, James D.
Abstract : Mutations in sarcomeric proteins have recently been established as heritable causes of Restrictive Cardiomyopathy (RCM). RCM is clinically characterized as a defect in cardiac diastolic function, such as, impaired ventricular relaxation, reduced diastolic volume and increased end-diastolic pressure. To date, mutations have been identified in the cardiac genes for desmin, α -actin, troponin I and troponin T. Functional studies in skinned muscle fibers reconstituted with troponin mutants have established phenotypes consistent with the clinical findings which include an increase in myofilament Ca 2 + sensitivity and basal force. Moreover, when RCM mutants are incorporated into reconstituted myofilaments, the ability to inhibit the ATPase activity is reduced. A majority of the mutations cluster in specific regions of cardiac troponin and appear to be mutational "hot spots". This paper highlights the functional and clinical characteristics of RCM linked mutations within the troponin complex.